Educación, sociedad y cultura : la controversia epistemológica - Jesús A. Valero Matas (Universidad de La Rioja, 2013)
This paper sets out a view of social reality, giving a brief analysis of the social changes that have taken place from the 60s up to the present day. During this period, society has felt the need to develop and provide new social services, but these have so far failed to resolve existing problems. The paper argues that institutions should give grater priority to social education, since the number of people nneding help is now so overwhelming that those in the caring professions are failing to meet their needs or to solve these pressing social problems.